Activation‐Induced Killer Cell Immunoglobulin‐like Receptor 3DL2 Binding to HLA–B27 Licenses Pathogenic T Cell Differentiation in Spondyloarthritis - Ridley, Anna (Arthritis Rheumatol, 2016)
OBJECTIVE: In the spondyloarthritides (SpA), increased numbers of CD4+ T cells express killer cell immunoglobulin‐like receptor 3DL2 (KIR‐3DL2). The aim of this study was to determine the factors that induce KIR‐3DL2 expression, and to characterize the relationship between HLA–B27 and the phenotype and function of KIR‐3DL2–expressing CD4+ T cells in SpA. METHODS: In total, 34 B27+ patients with SpA, 28 age‐ and sex‐matched healthy controls (20 B27− and 8 B27+), and 9 patients with rheumatoid arthritis were studied. KIR-3DL2 expression and other phenotypic characteristics of peripheral blood and synovial fluid CD4+ T cells were studied by flow cytometry, quantitative polymerase chain reaction, and Western blotting. T cell receptor clonality was determined by template‐switch anchored reverse transcription–polymerase chain reaction and sequencing analysis. Cytokines were measured by enzyme‐linked immunosorbent assay. RESULTS: Cellular activation induced KIR‐3DL2 expression on both naive and effector CD4+ T cells. KIR‐3DL2 binding to B27+ cells promoted expression of KIR‐3DL2, the Th17‐specific transcription factor retinoic acid receptor–related orphan nuclear receptor γt, and the antiapoptotic factor B cell lymphoma 2. KIR‐3DL2+CD4+ T cells in patients with ankylosing spondylitis were oligoclonal and enriched for markers of T cell activation and for the gut homing receptor CCR9. In the presence of B27+ antigen‐presenting cells, KIR‐3DL2+CD4+ T cells produced less interleukin‐2 (IL‐2) but more IL‐17. This effect was blocked by HC10, an antibody that inhibits the binding of KIR‐3DL2 to B27 heavy chains. CONCLUSION: KIR‐3DL2 binding to HLA–B27 licenses Th17 cell differentiation in SpA. These findings raise the therapeutic potential of targeting HLA–B27–KIR‐3DL2 interactions for the treatment of B27+ patients with SpA.